Astragaloside IV promotes the eNOS/NO/cGMP pathway and improves left ventricular diastolic function in rats with metabolic syndrome. Issue 1 (January 2020) - Lin, Xin; Wang, Qiongying; Sun, Shougang; Xu, Guangli; Wu, Qiang; Qi, Miaomiao; Bai, Feng; Yu, Jing
Objectives: This study aimed to explore the effects of astragaloside IV on metabolic syndrome induced by a high-fructose/high-fat diet in rats. Methods: Rats were randomized into four groups: normal control, metabolic syndrome, metabolic syndrome + intraperitoneal astragaloside 0.5 mg/kg/day, and metabolic syndrome + intraperitoneal astragaloside 2.0 mg/kg/day (n=30 per group) for 14 continuous days. Left ventricular functions were evaluated by hemodynamic and echocardiographic parameters. Results: Metabolic syndrome rats had a thicker interventricular septum and left ventricular posterior wall, accompanied by a higher E/A wave ratio, reduced E′ wave, increased A′ wave, decreased E′/A′ wave ratio, and higher E/E′ wave ratio. Astragaloside decreased insulin and triglyceride levels and improved diastolic dysfunction with no effects on systolic function. A high-fructose/high-fat diet also increased oxidative stress and decreased the myocardial endothelial nitric oxide synthase (NOS) dimer ratio, thus impairing nitric oxide (NO) production and reducing cyclic guanosine monophosphate (cGMP) production. Astragaloside increased NO and cGMP production in the myocardium and improved diastolic function. Conclusions: Astragaloside alleviated oxidative stress and restored NO signaling, thus improving myocardial left ventricular diastolic dysfunction in rats with metabolic syndrome. The underlying mechanisms could be associated with alleviation of oxidative stress and activation of the endothelial NOS/NO/cGMP pathway.